Sebagai Penghubung: Upaya Guru PAUD Kristen dalam Meningkatkan Minat Belajar Anak Usia Dini - Enafao Gea; Afandi Umbu Galla Lelu; Suardin Zai; Ruth Judica Siahaan; Edwin Goklas Silalahi; Marthen Mau (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Early childhood Christian education is an effort to form children's awareness from an early age in fostering a passion for learning to fill and develop themselves, so that they have the capacity, skills and skills to fear God. The purpose of writing this article is to explain the importance of the role of Christian PAUD teachers as liaisons in increasing early childhood interest in learning. The writing method uses a descriptive qualitative approach with a literature review method using books, journal articles and internet websites as references. The results of this study are that through the role of teachers as liaisons they can bring about changes in children who encourage them to seriously participate in the process of teaching and learning activities at school. Therefore, the teacher's role includes: 1) creating independent learning, 2) creating practical learning, 3) creating democratic learning, 4) creating ideal learning, 5) providing appreciation.